Variations in the slope of the psychometric functions for speech intelligibility: a systematic survey - MacPherson, Alexandra; Akeroyd, Michael A. (SAGE, 2014)
Although many studies have looked at the effects of different listening conditions on the intelligibility of speech, their analyses have often concentrated on changes to a single value on the psychometric function, namely, the threshold. Far less commonly has the slope of the psychometric function, that is, the rate at which intelligibility changes with level, been considered. The slope of the function is crucial because it is the slope, rather than the threshold, that determines the improvement in intelligibility caused by any given improvement in signal-to-noise ratio by, for instance, a hearing aid. The aim of the current study was to systematically survey and reanalyze the psychometric function data available in the literature in an attempt to quantify the range of slope changes across studies and to identify listening conditions that affect the slope of the psychometric function. The data for 885 individual psychometric functions, taken from 139 different studies, were fitted with a common logistic equation from which the slope was calculated. Large variations in slope across studies were found, with slope values ranging from as shallow as 1% per dB to as steep as 44% per dB (median = 6.6% per dB), suggesting that the perceptual benefit offered by an improvement in signal-to-noise ratio depends greatly on listening environment. The type and number of maskers used were found to be major factors on the value of the slope of the psychometric function while other minor effects of target predictability, target corpus, and target/masker similarity were also found.